The Policy Determinants of Investment in Tertiary Education - Oliveira Martins, Joaquim (OECD Publishing, 2007)
This paper assesses how policies and institutions affect private returns to invest in tertiary human capital, the ability of individuals to finance this investment and the institutional characteristics of tertiary education systems. Focusing on core tertiary education services, the paper presents new measures of private returns to tertiary education, the institutional setting for supplying tertiary education and the availability of individual financing in OECD countries. Using a panel of 19 countries, the number of new tertiary graduates (a proxy for investment in tertiary education) is regressed on these new proposed measures, as well as other standard determinants of investment in tertiary education. The resulting estimates are used to assess empirically the relative importance of several education, taxation and social policies affecting investment in tertiary education. Several avenues for reform and the trade-offs they present for public policy are discussed
Keywords: Economics